Kebijakan Negara Mmelakukan Pembatasan Internet di Papua dan Papua Barat dalam Putusan Nomor 230/G/Tf/2019/PTUN-JKT melalui Perspektif Hak Asasi Manusia - Kelvin Chandra; Tundjung Herning Sitabuana (Jurnal Syntax Transformation, 2022)
The case of restrictions on internet access in human rights policies has become the center of serious attention for the national and international community, because of the issue of internet restrictions that limit people's digital rights, one of which is the right to access communication and information. The riots that occurred in West Papua resulted in the termination of internet access, this was done so that the riots did not become wider. The government protects the public interest from various types of ITE abuse, one of which is the ability to stop access, but this also has the disadvantage of not regulating content, urgency and duration regulations. The purpose of the research is to find out the restrictions on internet access by the Government in Papua from a human rights perspective, and to find out the legal consequences and legal protection for Papuans against internet restrictions imposed by the Government. This research was conducted using normative legal research methods. The approach used in this research is the statutory approach, the case approach, and the conceptual approach. The findings of this study are the importance of government transparency to the public in carrying out these actions, and the importance of ensuring a sense of security and comfort in establishing open communication with the authorities. Not only is the act of restricting Internet access for no apparent reason, but in some cases also to protect national sovereignty and national security.